Antibacterial Hydrogels: Injectable and Self‐Healing Hydrogel with Anti‐Bacterial and Anti‐Inflammatory Properties for Acute Bacterial Rhinosinusitis with Micro Invasive Treatment (Adv. Healthcare Mater. 20/2020). Issue 20 (21st October 2020) - Chen, Zhengming; Cai, Zhengwei; Zhu, Chengjing; Song, Xianmin; Qin, Yanghua; Zhu, Minhui; Zhang, Tao; Cui, Wenguo; Tang, Haihong; Zheng, Hongliang
Abstract : In article number 2001032 by Haihong Tang, Hongliang Zheng, and co‐workers, an injectable and self‐healing hydrogel is first developed to treat acute bacterial rhinosinusitis based on high affinity and reversible combination between thiol and Ag + . This dynamic hydrogel with antibacterial and anti‐inflammatory properties is suitable for sinus micro invasive treatment which not only effectively eliminates pathogens, but also reduces mucosal edema. This approach provides a new strategy for avoiding systemic abuse of antibiotics.